Deconstructing a Leader: An In-Depth Analysis of the Commonalities between Plastic Surgery Chiefs and Chairmen. Issue 1 (July 2019) - Wenzinger, Eric; Weinstein, Brielle; Singh, Robinder; Reid, Christopher M.; Suliman, Ahmed; Herrera, Fernando A.
Abstract : Background: The authors sought to identify factors associated with current chiefs and chairpersons in academic plastic surgery to encourage and shape future leaders of tomorrow. Methods: Academic chairpersons in plastic surgery ( n = 94) were identified through an Internet-based search of all Accreditation Council for Graduate Medical Education–accredited residency training programs during the year 2015. Sex, ethnicity, academic rank, board certification, time since certification, medical school attended, residency program attended, fellowships training, advanced degrees, obtaining leadership roles at trainee's institution, and h -index were analyzed. Results: Of the 94 chiefs and chairpersons, 96 percent were male and 81 percent obtained full professor status, and 98 percent were certified by the American Board of Plastic Surgery. Mean time since certification was 22 years (range, 7 to 45 years). Fifty-one percent graduated from 20 medical schools, whereas 42 percent graduated from only nine plastic surgery training programs. Fifty-six percent had pursued fellowship beyond their primary plastic surgery training. Eighteen percent had obtained advanced degrees. Twenty-nine percent of chiefs and chairpersons obtained leadership roles at the institution where they had completed plastic surgery training. The mean h -index was 17.6 (range, 1 to 63). Graduates of the nine most represented residency programs had a mean h -index of 21 versus 15 when compared with the remaining chief/chairpersons ( p < 0.0062). Conclusion: Leaders in plastic surgery are more likely to be male, hold academic rank of professor, and have completed a fellowship after residency.